Grey Relational Analysis and Anova to Determine the Optimum Process Parameters for Friction Stir Welding of Ti and Mg Alloys - Sivam, S. P. Sundar Singh; Saravanan, Krishnaswamy; Pradeep, Nagaraj; Moorthy, Karuppiah Sathiya; Rajendrakumar, Sankarapandian (Periodica polytechnica. Mechanical engineering - Mas̆inostroenie, 2018)
The welding of Magnesium and Titanium and its alloys has continuously depicted a good challenge for designers and technologists. Ti and Mg alloys, particularly heat-treatable alloys, are difficult to join by fusion fastening techniques. The welding of dissimilar alloy such as Ti (Grade 2) and Mg (AZ91D) Alloy is an important problem during Friction Stir Welding (FSW). In this paper, the influence of Rotation speed (Rpm), Travel Speed (mm/min), Bottom Diameter Tool Pins (mm) and Tool Profiles of Ti and Mg alloy during FSW was investigated by Grey Relational Analysis and Anova was used to work out the foremost important Travel speed and feed rate affecting the Response. The primary and cooperation impact of the information factors on the normal reactions are examined. The expected values and measured values are genuinely close.